Diversification of Schistosoma japonicum in Mainland China revealed by mitochondrial DNA. - Qin Ping Zhao; Ming Sen Jiang; Hui Fen Dong; Pin Nie (Public Library of Science (PLoS), 2012)
BACKGROUND: Schistosoma japonicum still causes severe parasitic disease in mainland China, but mainly in areas along the Yangtze River. However, the genetic diversity in populations of S. japonicum has not been well understood across its geographical distribution, and such data may provide insights into the epidemiology and possible control strategies for schistosomiasis. METHODOLOGY/PRINCIPAL FINDINGS: In this study infected Oncomelania snails were collected from areas in the middle and lower (ML) reaches of the Yangtze River, including Hubei, Hunan, Anhui, Jiangxi and Jiangsu provinces, and in the upper reaches of the river, including Sichuan and Yunnan provinces in southwest (SW) China. The adult parasites obtained from experimentally infected mice using isolated cercariae were sequenced individually for several fragments of mitochondrial regions, including Cytb-ND4L-ND4, 16S-12S and ND1. Populations in the ML reaches exhibited a relatively high level of diversity in nucleotides and haplotypes, whereas a low level was observed for populations in the SW, using either each single fragment or the combined sequence of the three fragments. Pairwise analyses of F-statistics (Fst) revealed a significant genetic difference between populations in the ML reaches and those in the SW, with limited gene flow and no shared haplotypes in between. It is rather obvious that genetic diversity in the populations of S. japonicum was significantly correlated with the geographical distance, and the geographical separation/isolation was considered to be the major factor accounting for the observed difference between populations in the ML reaches and those in the SW in China. CONCLUSIONS: S. japonicum in mainland China exhibits a high degree of genetic diversity, with a similar pattern of genetic diversity as observed in the intermediate host snails in the same region in China.